A review of Andrés Álvarez and Juan Santiago Correa's (eds.) "Ideas y políticas económicas en Colombia durante el primer siglo republicano" (Ediciones Uniandes) - Erich Pinzón-Fuchs (Duke University, Center for the History of Political Economy (CHOPE), 2016)
A review of Andrés Álvarez and Juan Santiago Correa's book on the history of political and economic ideas in Colombia during the first century of the republic.
Keywords: B1; E00; H1; N16; 330; History of economics in Colombia; Colombian economic history; monetary history; institutional design